Secularism and biblical studies - Boer, Roland (BibleWorld, 2010)
Introduction: Secularism and the Bible / Roland Boer -- Part A: Initial engagement at the forum -- Scholarship and faith in Bible study / Michael V. Fox -- The unspeakable in biblical scholarship / Jacques Berlinerblau -- Part B: The manifesto debate -- A manifesto for biblical studies / Roland Boer -- Boer's manifesto : part of the solution or part of the problem : some reflections from a Swedish perspective / Hanna Stenstrum -- Guns do not kill, people do! (Mikhail Timofeyevich Kalashnikov) / Niels Peter Lemche -- Theological secularity : a response to Roland Boer / Mark G. Brett -- Is Boer among the prophets? : transforming the legacy of marxian critique / Todd Penner -- The end of biblical studies as a moral obligation / Hector Avalos -- Responsibilities to the publics of biblical studies and critical rhetorical engagements for a safer world / Joseph A. Marchal -- A German landscape : currents and credits of New Testament studies in Germany during the past decades / Heike Omerzu -- Private or public? the challenge of public theology to biblical studies / Philip Chia -- The paradoxes of secularism -- Neither religious nor secular : on saving the critic in biblical-criticism / Ward Blanton -- From Jefferson's Bible to Judge Moore's Ten commandments monument : ecularizing the Bible in the USA / Egar W. Conrad -- From ruth to foreign workers in contemporary Israel : a case study in the interaction of religion, politics and the economy / Athalya Brenner -- The Samaritans : biblical considerations in the solution of a political problem / Yairah Amit -- The biblical roots of secularism / Philip Davies